Evaluación del sistema de práctica pre-profesional de los estudiantes del tercer año de bachillerato del colegio técnico Alóag en la calidad de formación y propuesta de un sistema alternativo. - Pérez Ayala, Raúl Alfredo (2015)
Technical Education needs to consolidate its general education alternatives by gradually incorporating specific training in a determinate timing in workplaces. This study focuses on the possibility of implementing a system that will organize and supervise student's internships. It will be implemented with students of the Senior year of "Alóag" Highschool in Mejia, province of Pichincha. The hypothesis of this research demonstrated that more than 60% of the participants were not satisfied with the current system due to its flaws. Therefore, it demands a change. The theoretical framework discusses the evaluation, pre-professional practice, quality of training, organization and learning. The research method in this project woks with a research design crossed with literature and field work producing, as a result, a proper research proposal. A survey of seventy-seven participants including authorities, teachers and students. On the other hand, the objective of this research was to identify the limitations of the current system due to a geographical constraint related to the industrial development carried by numerous companies. Over 65% of the participants considered that there are serious limitations within the system of pre professional practices, that affects the implementation of a training profile. This proposal emphasizes on the idea that even high school have strengths in its faculty staff, laboratories and equipment; it lacks of a proper system that allows people to use these facilities. Since this is a social issue, approaching this reality will benefit the entire educational community.